Measuring radon concentrations in air at the progeny non-secular equilibrium time frame - Petropoulos, Nikolaos; Argyrou, Sotia (HNPS Advances in Nuclear Physics, 2023)
The Nuclear Engineering Laboratory of NTUA (NEL-NTUA) regularly tests radon-in-air concentration measuring instruments. Most common instruments involve open ionization chambers, radon absorbing devices and grab sampling devices. Most types of such instruments do not provide a calibrated radon concentration as soon as the air sampling has ended, since there should exist an adequate time gap, within which sampled radon would reach secular equilibrium with some or most of its immediate progeny. This gap should be around 10-20 min for radon to equilibrate with the Po-218 nucleus, or it could be more than about 3 hours for radon to equilibrate with the Bi-214 / Po-214 progeny. However, if there could be organized calibration experiments at the progeny non-secular equilibrium state, there are some instrument cases, for which this time gap difficulty may be better understood and overcome. To this end, in this work, the Bateman differential equations for all gamma and alpha emitting radon daughters are solved for radon daughters activity at any given time between 0 min and 3 hours using a spreadsheet. This would allow for obtaining a calibration correction factor to be applied at any given time before equilibrium, resulting for radon concentration estimations without the limitations of waiting. Following this solution, the results were theoretically assessed in terms of applicability. Calibration experiments performed for ionization chambers, radon absorbents and Lucas Cells at various radon concentrations in air at the progeny non-secular equilibrium time frame corroborate the theoretical approach.